DEVELOPMENT A SUSTAINABLE BUSINESS MODEL FOR ANANDA SEVA DHARMA FOUNDATION THROUGH MARKETING AND ENTREPRENEURSHIP - I Wayan Adi Pratama; Luh Sri Damyanti; Diky Budiman (BINA CIPTA, 2025)
This study aims to develop a sustainable business model for the Ananda Seva Dharma Foundation, an orphanage located in Sangsit Village, Buleleng, Bali, by strengthening business management and marketing strategies for their home industry product, B'Onic. The foundation has potential in human resources and agricultural assets, but faces challenges in the form of unstable product sales, limited digital marketing, and the absence of a structured management system. To overcome these problems, a community service program was designed using the Triple Layer Business Model Canvas (TLBMC) approach, which integrates economic, social, and environmental values, combined with a digital marketing strategy. The activity methodology included socialization, training, and mentoring stages carried out over six months. The results of the activity showed that this program succeeded in increasing the foundation's business management capacity, strengthening brand identity, and expanding market reach through digital marketing. The foster children gained entrepreneurial skills, while the foundation achieved better organizational efficiency and broader market opportunities. Overall, this program contributes to promoting the financial independence of foundations and social impact through the integration of sustainable business practices and digital entrepreneurship. The novelty of this research lies in the combination of TLBMC with digital marketing in the context of community service, so that it can become a model that can be replicated by other social enterprises.